Investigation on Cable Rejuvenation by Simulating Cable Operation - Yue Xie; Yifeng Zhao; Shuzhen Bao; Pengyu Wang; Jiasheng Huang; Peng Wang; Gang Liu; Yanpeng Hao; Licheng Li (IEEE Access, 2020)
Further research on retired cable rejuvenation via heat treatment was investigated in this paper. Three retired cables with service year of 7, 15 and 30 years were used and annealed at different temperatures following two different heat treatment methods. In the first test, two short cables with a length of 5 m were prepared and cut into five equal segments. Four segments of each cable were annealed at 90, 95, 100, and 105 °C to simulate the cable operation. Then, the cross-linked polyethylene (XLPE) from the cable insulation was peeled, and the peels from the inner, middle and outer positions were selected and subjected to the differential scanning calorimetry (DSC), DC conduction current, and dielectric breakdown strength measurements. The thermal and electrical performance of these samples were analyzed, and the optimum annealing temperature was determined. In the second test, three identical long cables were connected to a transformer, joints, and terminals to build two experimental circuits. The cables were annealed at the optimum temperature determined in the first test. The same measurements were performed on XLPE samples taken from the same positions as those in the first test. The results showed that the short cables exhibited the best thermal and electrical performance when annealed at 95 °C. The three long cables annealed at 95 °C verified that the thermal and electrical properties of the cable insulation were significantly improved. The results of the two different annealing methods, which closely represent the actual cable operations, verified the feasibility that old cables without overheating history could be rejuvenated via heat treatment.